Matemática
Thaamyres
13

RESOLVA AS EQUAÇOES 5 [ 1 - X ] - 2 X + = - 3 [ 2 + X ] 2 X + [ 3 - X ] = 5 - [ 3 X - 1 ] 3[ 4 + x ] - 2 = 2 [ 3 x - 1 ] 3 [ 2 x- 1 ] - 2 [ x - 2 ] = - 4 [ x + 3 ]

+1
(1) Respostas
robsoncardoso

5(1-x) -2x = -3(2+x) 5 - 5x -2x = -6 - 3x 5x-2x +3x = -6 +5 8x-2x = -1 6x= -1 x= -1/6 2x + (3-x) = 5 - (3x-1) 2x + 3x = 5 - 3x -1 5x  -3x = 5 -1 7x = 4 x= 7/4 3(4+x) - 2 = 2 (3x-1) 12 + 3x - 2 = 6x - 2 3x +10 = 6x - 2 3x-6x= -2 -10 3x= -12 x= -12/3 x= -4 3(2x-1) - 2(x-2) = -4(x+3) 6x - 3 - 2x -4 = -4x -12 4x - 5 = -4x - 12 4x +4x = -12 +5 8x= -7 x= 7/8

Adicionar resposta